2021
DOI: 10.1590/s1678-3921.pab2021.v56.02321
|View full text |Cite
|
Sign up to set email alerts
|

Selection gains for the palm oil production from progenies of American oil palm with oil palm

Abstract: The objective of this work was to estimate the genetic parameters, correlations, and selection gains for the oil production of interspecific hybrids progenies between American oil palm, of ‘Manicoré’ origin, and oil palm, of ‘La Mé’ origin. Thirty-nine progenies were evaluated from the sixth to the ninth year after planting, for the productivity of fresh fruit bunches (PROD_FFB), oil content in the bunch (OCB), and palm oil productivity (PROD_OP). The genetic parameters and gains from direct (GDS) and indirect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The result of obtaining high Δg in selecting a genetic trait of interest suggests the possibility of identifying genotypes carrying genes of interest for good transmission (Fellahi et al 2020). Research conducted by Gomes Junior et al (2021) in oil palm cultivars reported a Δg of 6% for oil to bunch (OB) and the production of fresh fruit bunches (FFB). Studies carried out in Ecuador in dura × dura crosses recorded genetic gains for bunch number (BNO) of 5.8% and for FFB of 1.4% for the entire breeding cycle (Cedillo et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result of obtaining high Δg in selecting a genetic trait of interest suggests the possibility of identifying genotypes carrying genes of interest for good transmission (Fellahi et al 2020). Research conducted by Gomes Junior et al (2021) in oil palm cultivars reported a Δg of 6% for oil to bunch (OB) and the production of fresh fruit bunches (FFB). Studies carried out in Ecuador in dura × dura crosses recorded genetic gains for bunch number (BNO) of 5.8% and for FFB of 1.4% for the entire breeding cycle (Cedillo et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The success of breeding programs depends on genetic variability; in practice, the utility of genetic gain through selection allows for better breeding criteria for selecting genetically superior individuals (Gomes Junior et al 2021). In evaluating, selecting, and developing individuals who show genetic superiority in agronomic traits, estimating genetic gains becomes essential for the industry's success for different crops (Pavlotzky and Murillo 2014;Rocha et al 2021).…”
Section: Introductionmentioning
confidence: 99%